Brexit Event Impact on Bursa Malaysia - Mohammad, Aslam; T., Senthil Kumar (2020)
A referendum has been conducted in the British parliament whether the United Kingdom (UK) will remain in the European Union (EU). It is widely known as Brexit meaning the British exit from the European Union. This event has a reflective impact on the world economy, more specifically on many stock exchanges. British pound sterling got weakened sharply and stock markets around the world seem fragile on this event. Nevertheless, the effect ranged from no impact to high impact meaning not all the economies were affected in the same way. Only those economies were affected which had been substantially exposed to the British economy. Although Malaysia does not transact highly substantial trade and commerce with them, but still there is some moderate exposure to British investments in some sectors. In this study, Bursa Malaysia stock price movement during the Brexit event has been analyzed using the event study methodology. Highly ranked ten publicly traded companies is selected and their stock returns are compared with the KCI Market Index returns. The results indicate that the stock returns show an inclining trend while being highly volatile surrounding the Brexit event. However, the shock is absorbed soon with correction. It shows that the Brexit event does not have a statistically significant effect on Bursa Malaysia.